Leadership and work community – views of graduating dental students - Kauhanen, Milka (My University, 2023)
Purpose: This study aimed to find out what kinds of views and expectations dental students close to graduating have on leadership and work communities as well as how they expect to fulfill these expectations after completing a leadership course tailored for dental students. The influence of the course on students’ views of leadership was also investigated. Methodology: The research material comprised reflective essays written by 5th-year dental students who had participated in a leadership course. The essays were analyzed using qualitative content analysis. Findings: Before the course, most students had not considered seeking a leadership position in the future, but most described that their views of leadership had grown more positive as a result of completing the module. Students perceived interpersonal communication competence as the most important factor for leaders, the whole work community, and for themselves. They assessed that their biggest strengths were found in this area. The biggest challenges in adapting to a work community concerned the students’ professional identities, which were still taking shape at the time of graduation. Value: The need for leaders in healthcare professions is growing due to ongoing reforms, the development of new technologies and patient demands. Therefore, undergraduate leadership education is needed to ensure that students have knowledge of leadership and work communities. Graduating dental students’ views and expectations concerning leadership and work communities have not been widely explored. Students’ perceptions of leadership were positive after the course and helped students to realize their own potential in this area.
Keywords: dental education, dental student, interpersonal communication competence, leadership, work community